Enterprise Service Oriented Architectures Concepts, Challenges, Recommendations - McGovern, James; Sims, Oliver; Jain, Ashish; Little, Mark (The Enterprise Series, 2006)
Conventional wisdom of the "software stack" approach to building applications may no longer be relevant. Enterprises are pursuing new ways of organizing systems and processes to become service oriented and event-driven. Leveraging existing infrastructural investments is a critical aspect to the success of companies both large and small. Enterprises have to adapt their systems to support frequent technological changes, mergers and acquisitions. Furthermore, in a growing global market, these systems are being called upon to be used by external business partners. Technology is often difficult, costly and complex and without modern approaches can prevent the enterprise from becoming agile. Enterprise Service Oriented Architectures helps readers solve this challenge in making different applications communicate in a loosely coupled manner. This classic handbook leverages the experiences of thought leaders functioning in multiple industry verticals and provides a wealth of knowledge for creating the agile enterprise. In this book, you will learn: • How to balance the delivery of immediate business value while creating long-term strategic capability • Fundamental principles of a service-oriented architecture (find, bind and execute) • The four aspects of SOA (Production, Consumption, Management and Provisioning) • How to recognize critical success factors to implementing enterprise SOAs • Architectural importance of service registries, interfaces and contracts • Why improper service decomposition can hurt you later rather than sooner • How application design and integration practices change as architects seek to implement the "agile" enterprise About the Authors James McGovern is an enterprise architect for The Hartford. He is an industry thought leader and co-author of the bestselling book: A Practical Guide to Enterprise Architecture. Oliver Sims is a recognized leader in the architecture, design and implementation of service-oriented and component-based enterprise systems. He was a founding member of the OMG Architecture Board. He was co-author of the groundbreaking book: Business Component Factory. Ashish Jain is a Principal Architect with Ping Identity Corporation, a leading provider of solutions for identity federation. Prior to joining Ping Identity, he worked with BEA Systems where his role was to assist BEA customers in designing and implementing their e-business strategies using solutions based on J2EE. He holds several industry certifications from SUN and BEA and is also a board member for the Denver BEA User group. Mark Little is Director of Standards and SOA Manager for JBoss Inc. Prior to this, he was Chief Architect for Arjuna Technologies Ltd and a Distinguished Engineer at Hewlett-Packard. As well as being an active member of the OMG, JCP, OASIS and W3C, he is an author on many SOA and Web Services standards. He also led the development of the world's first standards-compliant Web Services Transaction product.